1989
DOI: 10.1093/sleep/12.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Patients with Spontaneous Panic Attacks

Abstract: Twenty-four drug-free patients with a DSM-III diagnosis of panic disorders (and their age- and sex-matched normal controls) slept in the laboratory for 3 consecutive nights. Panic patients showed a slightly longer sleep latency and a lower sleep efficiency than their normal controls. They also had more overall movement time and more body movements during stage 2 sleep. Eight panic attacks were recorded arising out of sleep. Six of them occurred in the transition phase between stage 2 and stage 3 sleep. The noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
9

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 0 publications
1
66
0
9
Order By: Relevance
“…They also feature apprehension and somatic symptoms, similar to panic attacks that are triggered during wake states. Studies that have captured sleep panic attacks during polysomnographic recordings find that the episodes were preceded by either stage 2 or stage 3 of non-REM sleep (17,27). Mellman et al (17) more specifically noted that the sleep panic attacks originated during the transition from stage 2 into early slow wave sleep which is a period of diminishing arousal.…”
Section: Sleep Panic Attacksmentioning
confidence: 99%
“…They also feature apprehension and somatic symptoms, similar to panic attacks that are triggered during wake states. Studies that have captured sleep panic attacks during polysomnographic recordings find that the episodes were preceded by either stage 2 or stage 3 of non-REM sleep (17,27). Mellman et al (17) more specifically noted that the sleep panic attacks originated during the transition from stage 2 into early slow wave sleep which is a period of diminishing arousal.…”
Section: Sleep Panic Attacksmentioning
confidence: 99%
“…Uykudaki bu sonuçlar panik bozukluğunda öncesinde yapılan çalışma sonuçları ile uyumludur (27)(28)(29)(30)(31). Uykunun devamlılığının bozulduğuna dair bu bulgular diğer psikiyatrik bozukluklarda da görülen, herhangi bir psikiyatrik bozukluğa özgün olmayan bulgulardır (32).…”
Section: Discussionunclassified
“…129-130). Findings suggest that panic attacks may occur in the absence of catastrophic thoughts as well; for example, a number of investigators found that panic attacks occur during the non-dreaming stages of sleep, where catastrophic thoughts are absent (Craske & Barlow, 1989;Craske & Rowe, 1997;Hauri, Friedman, & Ravaris, 1989;Lesser, Poland, Holcant, & Rose, 1985;Ley, 1988;Mellman & Uhde, 1989). Although Schredl, Kronenberg, Nonnell and Heuser (2001) reported that nocturnal panic attacks are closely related to dreams and nightmares, they too reported that a subgroup of patients in their study experienced panic attacks in the absence of dreams.…”
Section: Misinterpretation Theorymentioning
confidence: 96%
“…However, as noted above, the existence of catastrophic beliefs does not necessarily prove a causal relationship, especially because panic attacks may occur in absence of catastrophic thought (Craske & Rowe, 1997;Hauri et al, 1989;Ley, 1988;Mellman & Uhde, 1989).…”
Section: Strengths and Weaknesses Of Traditional Theoriesmentioning
confidence: 99%